Growth response of calcifying marine epibionts to biogenic pH fluctuations and global ocean acidification scenarios - Johnson, Mildred; Hennigs, Laura Margarethe; Sawall, Yvonne; Pansch, Christian; Wall, Marlene (Limnology and Oceanography, 2021)
In coastal marine environments, physical and biological forces can cause dynamic pH fluctuations from microscale (diffusive boundary layer [DBL]) up to ecosystem‐scale (benthic boundary layer [BBL]). In the face of ocean acidification (OA), such natural pH variations may modulate an organism's response to OA by providing temporal refugia. We investigated the effect of pH fluctuations, generated by the brown alga Fucus serratus' biological activity, on the calcifying epibionts Balanus improvisus and Electra pilosa under OA. For this, both epibionts were grown on inactive and biologically active surfaces and exposed to (1) constant pH scenarios under ambient (pH 8.1) or OA conditions (pH 7.7), or (2) oscillating pH scenarios mimicking BBL conditions at ambient (pH 7.7–8.6) or OA scenarios (pH 7.4–8.2). Furthermore, all treatment combinations were tested at 10°C and 15°C. Against our expectations, OA treatments did not affect epibiont growth under constant or fluctuating (BBL) pH conditions, indicating rather high robustness against predicted OA scenarios. Furthermore, epibiont growth was hampered and not fostered on active surfaces (fluctuating DBL conditions), indicating that fluctuating pH conditions of the DBL with elevated daytime pH do not necessarily provide temporal refugia from OA. In contrast, results indicate that factors other than pH may play larger roles for epibiont growth on macrophytes (e.g., surface characteristics, macrophyte antifouling defense, or dynamics of oxygen and nutrient concentrations). Warming enhanced epibiont growth rates significantly, independently of OA, indicating no synergistic effects of pH treatments and temperature within their natural temperature range.